Strategies of Verbalization of Epistemic Responsibility in Mass Media Discourse of Informational Confrontation (by Example of Coverage of the Ukrainian Crisis) - A. I. Chepurnaya (Научный диалог)
Strategies of verbalization of epistemic responsibility in the Russian and American media discourse are considered. The material of the study were the texts published in the Internet versions of the Russian and American media, which covers the Ukrainian crisis. Discursive and content analysis methods are used. The relevance of the study is due to the modern features of functioning of Russian and foreign media systems, referred to as information war. The typology of strategies of epistemic responsibility verbalization is proposed, which includes two strategies, coupled with high epistemic responsibility (a statement of fact and implicit assertion), and three strategies for avoiding epistemic responsibility (personification of information / an expert speaks / from the horse’s mouth, darkening of information source, word of mouth). The statistical analysis of the implementation of the identified strategies in the fragments of the Russian and American media discourse is carried out. A general tendency to the predominance of the strategy of “statement of fact” is shown, the next being the strategy of “personification information / an expert speaks / from the horse’s mouth.” The conclusion is made about the possible dependence of the obtained results on the affiliation of the analyzed works of the media discourse to news journalism, which operates with facts, ready-made results of knowledge, in contrast to analytical journalism, designed to interpret, explain, discuss.